A self-consistent model for temperature and current distribution in abrupt heterojunction bipolar transistors. - Anwar, A.F.M.
The thermal behavior of abrupt heterojunction bipolar transistors (HBTs) has been studied by coupling the thermionic-field-emission injection mechanism at the emitter-base heterojunction with the thermal-electric feedback phenomenon. The exact quantum mechanical injection mechanism rather than the semiclassical WKB approximation is used in the present calculation to self-consistently calculate the thermionic and tunneling components of current. Moreover, the total current and temperature are self-consistently evaluated by testing the convergence on both current and temperature. The calculation shows correctly that the degree of the partitioning between the thermionic and tunneling components are bias- as well as temperature-dependent. It is shown that even a single emitter finger can have a highly nonuniform temperature and current distribution across it, leading to the current collapse phenomenon. At high power levels, this may give rise to a current collapse phenomenon similar to that observed for the multifinger HBTs.
Keywords: Abrupt HBTs; Abrupt heterojunction bipolar transistors; Bias-dependent current partitioning; Current collapse phenomenon; Emitter-base heterojunction; Exact quantum mechanical injection mechanism; High power levels; Multifinger HBTs; Nonuniform current distribution; Nonuniform temperature distribution; Self-consistent model; Single emitter finger HBTs; Temperature-dependent current partitioning; Thermal behavior; Thermal-electric feedback phenomenon; Thermionic current component; Thermionic-field-emission injection mechanism; Tunneling current component